LIGHT SCATTERING STUDIES OF CUPRUM OXIDE WATER SUSPENSIONS - Garibyan, Boris; Kohlert, Victoria (Revista Inclusiones, 2020)
In this work, stimulated low-frequency Raman scattering (SLFRS), caused by laser pulses interaction with nanoparticles acoustic vibrations was registered in water suspension of Cu oxide nanoparticles. SLFRS conversion efficiency and threshold are measured. It was found that frequency shifts of the scattered light from the exciting light are located in gigahertz range